Mahmud Yunus in the Book of Ilmu Mustholah Hadis: An Analysis of His Thought and Influence from the Treasury of Middle Eastern Scholars - Junus, Ihsan Jamaluddin; Dadah, Dadah (Green Publisher Indonesia, 2026)
This study examines the Book of Mustholah Hadith by Mahmud Yunus as one of the important works that played a role in the formation of the initial framework of hadith studies in Indonesia. The focus of the research includes: (1) the characteristics of the book of Mustholah Hadith, (2) the thought of Mahmud Yunus in formulating the concepts of hadith science, and (3) the relationship of this thought with the scientific tradition of Middle Eastern scholars. This study uses a qualitative-descriptive method with a content analysis approach. Data was collected through literature studies, mainly by examining the works of Mahmud Yunus and comparing them with the classic musthalah al-hadith books as well as references to modern Middle Eastern scholars. The results of the study show that Mahmud Yunus' work is compiled systematically and concisely in a didactic style, so it is suitable for beginner students. His thinking was heavily influenced by the works of Middle Eastern scholars such as Ibn al-Salah, al-Nawawi, and al-Suyuthi, but he rearranged the material to be simpler and in accordance with the Indonesian educational context of his time. Thus, this book serves as an intellectual bridge between the Middle Eastern scientific tradition and the needs of hadith learning in Indonesia.